PLANAR WPT SYSTEMS FOR IOT AND FOD APPLICATIONS - Shaldybayev, Daryn (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Wireless Power Transfer (WPT) has become a critical enabling technique for the continuous use of low-power electric items in intelligent surroundings. Researchers have focused on smaller and more efficient WPT solutions due to their demand in applications ranging from the Internet of Things (IoT) to biomedical settings, where reliable power transfer across different frequencies is required. For example, planar coil-based WPT systems have shown to be favorable, due to the their low profile, manufacturability using standard printed circuit board (PCB) processes, and ability to be integrated into different form factors. In this work, we design, analyse, and validate a dual-band planar WPT system operating at 0.9 GHz and 1.8 GHz. Different from classical single-band structures in pursuit of solely power or data transmission, the dual-band configuration provides concurrent functioning over several frequencies. It enhances the efficiency of power delivery while facilitating data communication functionalities. The compact planar invisibility resonators produced (30 × 30mm2) are optimized through analytical and simulation-based methods to ensure robust coupling and resonance characteristics. The proposed system achieves power transfer efficiencies (PTE) of 74% and 66% at their corresponding frequencies. Moreover, performance metrics such as PTE allow for an intuitive evaluation of system performance, whereas the Figure-of-Merit (FoM) offers a comprehensive assessment. This thorough procedure is aimed at providing a safe experience for users while also ensuring reliable operation, as the Foreign Object Detection (FOD) mechanism integrated into the system allows it to detect and react to extraneous materials in the charging zone as required. Not only does this reduce any potential hazards, but it also maintains the efficiency of the wireless link.
Keywords: Dual-band functionality; misalignment; Power transfer efficiency; Wireless power transfer; op; type of access: embargo